On Human-Nature Relations: The Importance of Malay Adat and Rituals in Protecting the Suhaid River in West Kalimantan, Indonesia - Suprianto, Bibi (Islamic Studies Review, 2023)
Many scholars have examined human-nature relations through various frameworks. A few researchers, however, have studied human-nature relations through Malay adat (custom) and rituals concerning the Suhaid river in Kapuas Hulu, West Kalimantan. The purpose of this study is to examine whether the relationship between humans and nature is made significant through Malay adat and rituals that protect rivers. This study uses manuscript data, interviews, and observations in Suhaid of Kapuas Hulu regency in West Kalimantan. The respondents consisted of the head of the Malay traditional court, village religious leaders, and the local Malay community. In addition, researchers also used an anthropological approach to study Malay culture. This study shows that the relationship between humans and nature in the river illustrates: 1) adat and rituals have local values ​​and beliefs which protect rivers; 2) the Suhaid Malay community is concerned with protecting rivers; 3) Malay customary laws aimed at maintaining the relationship between humans and nature were developed as part of a peace treaty between Pangeran Suma Dilaga and the Iban people; and 4) the contemporary relationship between humans and nature in the Suhaid river has been outlined in customary law (hukum adat) and is practiced in the tradition of buang-buang rituals. The researcher's findings highlight the importance of Malay adat and rituals in the conservation of the Suhaid river in West Kalimantan.